Post-mortem biochemistry differences between vitreous humour and cerebrospinal fluid. Issue 5 (2nd September 2020) - Garland, J.; Philcox, W.; McCarthy, Sinead; Kesha, K.; Lam, L.; Spark, A.; Palmiere, C.; Elstub, H.; Cala, A.D.; Stables, S.; Tse, R.
ABSTRACT: Cerebrospinal fluid (CSF) and vitreous humour (VH) can be biochemically analysed post-mortem. CSF can be aspirated from the ventricular system (VA) and from lumbar puncture (LP), whereas, VH is aspirated from the orbits. This study compared the biochemical constituents between CSF and VH in 20 post-mortem subjects as well as the effect post-mortem interval and subject age have on these variables. VH samples had significantly higher sodium (Na) and chloride (Cl) and lower magnesium (Mg), potassium (K), urea (Ur) and creatinine (Cr) compared with CSF samples. No statistically significant difference was demonstrated with beta-hydroxybutyrate (BHB) and glucose levels in both VH and both CSF samples. Interestingly, some of the differences in the biochemical analysis correlated with age, but none with post-mortem interval. In addition to sampling and pre-analytical sample processing differences, there may also be ante- and post-mortem factors explaining these observations. This study suggests that post-mortem CSF and VH are biochemically different and reference ranges for VH are not recommended for use in CSF samples.